Problems and Prospects of Vegetables Farming in Kalika Municipality - Dhakal, Chandra Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Vegetable is one of the important cash crops of Nepal; however, contribution of vegetable in national GDP is not so high. Nepal Rastra Bank Report 2023 showed that vegetable contributed the 9.7percent of total GDP of the nation. In Kalika municipality 77% population followed agriculture as main profession. All of them are involved in vegetable farming. In this context, the study analyzed the problems and prospects of vegetable farming in Kalika municipality. The study followed the mixed method research design. Both primary and secondary source of data were used in this study. Findings and conclusion of this study is based on primary data. From the analysis data analysis, it is found that there Kalika Municipality can be pocket area of organic vegetable farming; however, government has only provided limited supported for vegetable farming. There are various problems existed in vegetable farming such as irrigation, disease and market. If these problem in time there will be increased the quality and quantities of vegetable production in study area.